Face Detection Analysis of Digital Photos Using Mean Filtering Method - Sunardi, Sunardi; Yudhana, Anton; Wijaya, Setiawan Ardi (Universitas Dharma Wacana, 2022)
Face detection in digital photos aims to get the face area in the digital photo. Usually, a lot of noise occurred when detecting faces in digital photos. This study applies the mean filtering method to improve digital photos by reducing noise. The accuracy of the mean filtering method is calculated using a confusion matrix, while the ability of this method is measured using the parameters of Mean Square Error (MSE) and Peak Noise to Signal Ratio (PNSR). Viola-Jones method was used to detect faces in this research. This method was chosen because it is one of the face detection procedures with high accuracy and good computational ability. Testing the mean filtering method obtained the lowest MSE of 9.33, while the highest PNSR of 14.37. The accuracy obtained by the mean filtering method using confusion is 90%. Based on these results, it can be concluded that the mean filtering method is feasible to be used in the case of face detection in digital photos.